Henry S. Pritchett papers - Pritchett, Henry S. (Henry Smith), 1857-1939.; Pritchett, Henry S. (Henry Smith), 1857-1939.
Correspondence, speeches, writings, reports, travel diaries, autobiographical material, Pritchett's book entitled What is Religion? (1906), and other papers relating to Pritchett's career in science and education. Documents his activities with the Carnegie Foundation for the Advancement of Teaching, Massachusetts Charles River Basin Commission, Santa Barbara Relief Fund Committee, formation of the U.S. Bureau of Standards, and the Franklin Fund. Subjects include education, medical education, racial matters, political affairs, Theodore Roosevelt, and Woodrow Wilson. Correspondents include Charles Francis Adams, Samuel Bowles, Nicholas Murray Butler, Andrew Carnegie, Charles Gates Dawes, Charles William Eliot, Samuel S. Hall, Herbert Hoover, Walter A. Jessup, Frederick P. Keppel, William S. Learned, Gladys Noon, Margaret Rabitte, Alfred Zantzinger Reed, Theodore Roosevelt, Elihu Root, Elihu Root, Jr., W.B. Storey, William H. Taft, Booker T. Washington, Woodrow Wilson, and Owen Wister.
Astronomer, superintendent of the U.S. Coast and Geodetic Survey, and president of Massachusetts Institute of Technology.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Charles Francis, -- 1835-1915 -- Correspondence; Bowles, Samuel, -- 1826-1878 -- Correspondence; Butler, Nicholas Murray, -- 1862-1947 -- Correspondence; Carnegie, Andrew, -- 1835-1919 -- Correspondence; Dawes, Charles Gates, -- 1865-1951 -- Correspondence; Eliot, Charles William, -- 1834-1926 -- Correspondence; Hall, Samuel S. -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Jessup, Walter A. -- 1877-1944 -- Correspondence; Keppel, Frederick P. -- 1875-1943 -- Correspondence; Learned, William S. -- 1876-1950 -- Correspondence; Rabitte, Margaret -- Correspondence; Reed, Alfred Zantzinger, -- 1875-1949 -- Correspondence; Roosevelt, Theodore, -- 1858-1919.; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Root, Elihu, -- 1881-1967 -- Correspondence; Storey, W. B. -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Washington, Booker T., -- 1856-1915 -- Correspondence; Wilson, Woodrow, -- 1856-1924.; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Wister, Owen, -- 1860-1938 -- Correspondence; Massachusetts. -- Charles River Basin Commission; United States. -- Bureau of Standards; Carnegie Foundation for the Advancement of Teaching; Franklin Fund; Massachusetts Institute of Technology; Santa Barbara Relief Fund Committee; U.S. Coast and Geodetic Survey; Astronomy; Disaster relief -- California; Earthquakes -- California -- Santa Barbara; Education; Education -- Societies, etc; Endowments; Medicine -- Study and teaching; Religious literature; Rivers -- Massachusetts; Science; United States -- Politics and government -- 1901-1953.; United States -- Race relations; Astronomers; Educators; Public officials